Bismuth simple substance and oxygen deficiency co-modified bismuth titanate nanosheet as well as preparation method and application thereof
The bismuth titanate nanosheet catalyst co-modified with bismuth elemental and oxygen defects has solved the problem of low NOx purification efficiency in existing photocatalytic technology, and achieved efficient and stable photocatalytic removal of nitrogen oxides.
Patent Information
- Application Number
- CN202411804829.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-11
AI Technical Summary
When removing nitrogen oxides (NOx), existing photocatalytic technology has problems such as low light absorption efficiency, low separation and migration efficiency of electron-hole pairs, and low surface redox reaction efficiency, resulting in low purification efficiency.
The preparation method of a bismuth titanate nanosheet catalyst comodified by bismuth elemental and oxygen defect includes dispersing the precursor of bismuth and titanium in an alkaline solution, adding surfactant and reacting in an oven, and then mixing with a reducing agent at room temperature to obtain bismuth elemental and oxygen defect comodified by bismuth elemental and oxygen defect by wet chemical deposition.
The catalyst exhibits stable and efficient catalytic performance under light conditions, significantly improving the deep purification capacity of NOx. Compared with the unmodified Bi4Ti3O12 catalyst, the NO removal rate and NO2 generation amount are significantly improved.
Smart Images

Figure CN119591149A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalysis, and specifically relates to a bismuth titanate nanosheet catalyst co-modified with bismuth element and oxygen defects, a preparation method thereof, and an application in photocatalytic removal of nitrogen oxides. Background Art
[0002] The large-scale and rapid development of industry has caused environmental pollution. Nitrogen oxides (NOx), as a typical pollutant gas in the atmosphere, can easily induce photochemical smog, form acid rain, destroy the ozone layer, etc., seriously endangering the ecological environment and human health. x Removal technologies include catalytic combustion, chemical absorption and physical adsorption, but they usually require the participation of precious metal catalysts and cause excessive energy consumption, or the removal process is prone to secondary environmental pollution. Photocatalytic technology driven by light energy has the characteristics of extremely low energy consumption, mild reaction conditions, and green sustainability, and is widely used in the field of environmental pollutant control. Photocatalytic technology can oxidize NOx into nitrates on the catalyst surface, which has good application prospects.
[0003] After more than half a century of development, photocatalytic technology still faces three major bottleneck problems: low light absorption efficiency, low efficiency of separation and migration of electron-hole pairs, and low efficiency of surface redox reactions. In response to this, researchers have improved the separation, migration and utilization efficiency of photogenerated carriers by adjusting the electronic structure of materials and controlling the surface microstructure of materials. Currently, the widely studied general metal oxides (such as TiO2), metal sulfides (such as CdS), non-metallic semiconductor materials (such as g-C3N4), etc., generally have the problems of low efficiency in utilizing sunlight, easy recombination of photogenerated electron-hole pairs, and insufficient surface redox ability, resulting in insufficient oxidation performance of photocatalytic purification of NOx, and even the production of more toxic byproducts NO2, which is not conducive to the practical application of photocatalytic technology.
[0004] The material structure of bismuth-based semiconductors is composed of alternating bismuth oxide layers and perovskite-like layers. Its valence band is formed by the hybridization of Bi 6s and O2p orbitals. It is easy to reduce the band gap width by adjusting the valence band position, and its photoelectric performance is improved after surface modification. 12 As a bismuth-based Aurivilius type semiconductor material, the band gap width is generally around 3.0 eV. In theory, its light response range can be improved through ion doping, metal loading and structural defects, increasing the absorption of visible light and promoting the separation of photogenerated electron-hole pairs and their migration to the surface of the material to participate in redox reactions. 12The surface photoelectric performance of the material still needs to be improved, and the surface active free radicals are insufficient or the oxidation capacity is limited, resulting in the efficiency of photocatalytic NOx purification is still not high. Therefore, the present invention carries out targeted modification and preparation to improve its efficiency in high-efficiency and deep purification of NOx. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a method for preparing a bismuth titanate nanosheet catalyst co-modified with bismuth and oxygen defects, the raw materials of which are easily available and the preparation method is simple; the second purpose of the present invention is to provide a Bi4Ti3O 12 The catalyst has stable catalytic performance and high catalytic efficiency under light conditions; the third object of the present invention is to provide Bi4Ti3O co-modified with the bismuth element and oxygen defects 12 Application of catalysts in photocatalytic removal of NOx.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A method for preparing bismuth titanate nanosheets co-modified with bismuth element and oxygen defects comprises the following steps:
[0008] 1) Dispersing bismuth and titanium precursors in an alkaline solution in sequence to obtain a bismuth-titanium suspension;
[0009] 2) adding a surfactant to the bismuth-titanium suspension, and reacting the suspension at a constant temperature in an oven to obtain bismuth titanate nanosheets;
[0010] 3) The reducing agent and the bismuth titanate nanosheets are dispersed in deionized water respectively, and mixed with magnetic stirring at room temperature to obtain bismuth titanate nanosheets co-modified with bismuth element and oxygen defects by wet chemical deposition.
[0011] In some embodiments, the bismuth precursor is bismuth nitrate.
[0012] In some specific embodiments, the titanium precursor is tetrabutyl titanate.
[0013] In some embodiments, the surfactant is sodium oleate.
[0014] In certain specific embodiments, the process conditions of the oven constant temperature reaction in step 2) are: reaction temperature is 180° C., and reaction time is 20 h.
[0015] In certain specific embodiments, the ratio of the mass of the bismuth precursor to the volume of the titanium precursor in step 1) is (1-2) g: (0.5-1.5) mL.
[0016] In certain specific embodiments, in step 3), the molar ratio of the reducing agent to the bismuth titanate nanosheets is (0.2-0.6):1; and the reducing agent is sodium borohydride.
[0017] A bismuth titanate nanosheet co-modified with bismuth element and oxygen defects prepared by the aforementioned preparation method.
[0018] The invention discloses an application of bismuth titanate nanosheets co-modified with the above-mentioned bismuth element and oxygen defects in photocatalytic removal of nitrogen oxides.
[0019] Compared with the prior art, the present invention has at least the following advantages:
[0020] The preparation method of bismuth titanate nanosheets co-modified with bismuth element and oxygen defects provided by the present invention comprises the following steps: 1) dispersing bismuth and titanium precursors in alkaline solution in sequence to obtain bismuth titanium suspension; 2) adding surfactant to the bismuth titanium suspension, reacting in an oven at a constant temperature to obtain bismuth titanate nanosheets; 3) dispersing the reducing agent and the bismuth titanate nanosheets in deionized water respectively, mixing and magnetically stirring at room temperature, and obtaining bismuth titanate nanosheets co-modified with bismuth element and oxygen defects by wet chemical deposition. The preparation method has simple steps, readily available raw materials, and excellent performance; the obtained bismuth titanate nanosheets co-modified with bismuth element and oxygen defects, the synchronous construction of bismuth element and oxygen defects can greatly enhance the material's absorption of light and promote the separation of photogenerated electron-hole pairs.
[0021] 2) The bismuth titanate nanosheets of the present invention are used for photocatalytic removal of nitrogen oxides. The bismuth titanate nanosheet photocatalyst co-modified with bismuth and oxygen defects is successfully constructed, and the SPR effect of bismuth is effectively utilized to enhance the Bi4Ti3O 12 The absorption of light and the synchronously constructed oxygen defects have localized electron capabilities, which can improve the efficiency of carrier separation and promote the generation of active free radicals, further improving the modified Bi4Ti3O 12 Compared with the same type of photocatalysts reported in other patents, the photocatalyst provided by the present invention has a simple preparation method and excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0023] Figure 1 Bi4Ti3O prepared in Example 1 12 XRD pattern of the catalyst;
[0024] Figure 2 Bi4Ti3O prepared in Example 1 12TEM and HRTEM images of the catalyst;
[0025] Figure 3 The Bi / Bi4Ti3O prepared in Example 2 12 -XRD pattern of OVs catalyst;
[0026] Figure 4 The Bi / Bi4Ti3O prepared in Example 2 12 -TEM and HRTEM images of OVs catalyst;
[0027] Figure 5 Bi4Ti3O 12 and Bi / Bi4Ti3O 12 -EPR diagram of OVs catalyst;
[0028] Figure 6 Bi4Ti3O 12 and Bi / Bi4Ti3O 12 - Fluorescence lifetime diagram of OVs catalyst;
[0029] Figure 7 Bi4Ti3O 12 and Bi / Bi4Ti3O 12 -Photocurrent diagram of OVs catalyst;
[0030] Figure 8 Bi4Ti3O 12 and Bi / Bi4Ti3O 12 -NO concentration variation diagram of photocatalytic degradation of NO by OVs catalyst within 30 minutes;
[0031] Fig. 9 Bi4Ti3O 12 and Bi / Bi4Ti3O 12 -NO2 concentration variation diagram within 30 minutes of photocatalytic degradation of NO by OVs catalyst;
[0032] Fig.10 for Bi / Bi4Ti3O 12 - Reaction cycle test diagram of OVs catalyst photocatalytic degradation of NO;
[0033] Fig.11 Bi / Bi4Ti3O with different bismuth and oxygen vacancy concentrations 12 -NO concentration variation diagram of photocatalytic degradation of NO by OVs catalyst within 30 minutes;
[0034] Fig.12 Bi / Bi4Ti3O with different bismuth and oxygen vacancy concentrations 12-OVs catalyst photocatalytic degradation of NO within 30 minutes. DETAILED DESCRIPTION
[0035] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0036] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0037] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0038] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0039] In the following embodiments, the bismuth nitrate raw material is analytically pure, specifically purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the tetrabutyl titanate raw material is analytically pure, specifically purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the sodium oleate raw material is analytically pure, specifically purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the sodium hydroxide raw material is analytically pure, specifically purchased from Sinopharm Chemical Reagent Co., Ltd.
[0040] The test methods used in the following embodiments include:
[0041] The photoelectric properties and surface redox properties of the material are reflected by testing the main properties of each test sample respectively; the main properties tested in this application include phase structure, microscopic morphology, relative concentration of oxygen defects, carrier fluorescence lifetime, photocurrent intensity, photocatalytic NO oxidation, etc.
[0042] 1) X-ray diffraction spectrum test;
[0043] Use X-ray diffraction equipment to test the crystal structure of the sample according to the X-ray diffraction analysis method specified by the national standard or laboratory. ;
[0044] 2) Transmission electron microscopy test
[0045] Use transmission electron microscopy equipment to perform high-resolution testing of the nanostructure and morphology of samples in accordance with relevant operating specifications;
[0046] 3) Electron paramagnetic resonance test
[0047] Electron paramagnetic resonance equipment is used to conduct magnetic tests on unpaired electrons in the sample according to the EPR standard method to analyze its electronic structure and defect characteristics;
[0048] 4) Time-resolved fluorescence lifetime test
[0049] Using a time-resolved fluorescence lifetime analysis instrument, the fluorescence lifetime of the sample is tested according to the standard method of fluorescence lifetime measurement to obtain its photophysical properties;
[0050] 5) Photocurrent test
[0051] The photocurrent test system is used to test the photoelectric conversion performance of the sample according to the experimental method of photocurrent response measurement to evaluate its photocurrent characteristics;
[0052] 6) Photocatalytic NO oxidation test
[0053] A photocatalytic reactor and a nitrogen oxide analyzer were used to test the photocatalytic activity of the samples according to the experimental standards for photocatalytic NO oxidation, and their efficiency in NO oxidation was evaluated.
[0054] Example 1: Preparation of original Bi4Ti3O 12 catalyst
[0055] Original Bi4Ti3O 12 The specific method for preparation is as follows:
[0056] 1) Weigh 10g NaOH and dissolve it in 50mL deionized water to prepare an alkaline solution; weigh 1.65g Bi(NO3)3·5H2O and pour it into the alkaline solution, and disperse it by ultrasonic magnetic stirring for 10min to obtain a suspension; weigh 0.88mL C 16 H 36 O4Ti was quickly dropped into the above suspension, and ultrasonic magnetic stirring was performed again for 10 min to obtain a titanium-bismuth suspension;
[0057] 2) Add 0.03g C to the titanium bismuth suspension 17 H 33 CO2Na, after magnetic stirring at room temperature for 60 min, transferred to an oven and kept reacting at 180 °C for 20 h; the precipitate obtained after the reaction was washed with deionized water and ethanol to remove soluble impurities, and dried at 60 °C for 12 h to obtain the original Bi4Ti3O 12 Nanosheet powder.
[0058] The original Bi4Ti3O 12 Phase analysis XRD diagram Figure 1 As shown, TEM and HRTEM Figure 2 As shown. Figure 1 and Figure 2 It can be seen from the figure that the diffraction peaks corresponding to each crystal plane are 12 The diffraction peaks of the standard card correspond one to one, Bi4Ti3O 12 The catalyst is in the form of nanosheets. The preparation method of this application successfully obtained Bi4Ti3O 12 Nanosheet powder.
[0059] Example 2: Preparation of bismuth titanate nanosheet catalyst co-modified with bismuth and oxygen defects
[0060] Bi / Bi4Ti3O 12 -OVs preparation, the specific method is as follows:
[0061] 1) Weigh 1.0 g of the original Bi4Ti3O prepared in Example 1 12 The nanosheet powder was added into 50 mL of deionized water and stirred for 30 min to obtain Bi4Ti3O 12 Suspension;
[0062] 2) In Bi4Ti3O 12 In the suspension, 20 mL of NaBH4 solution (NaBH4 / Bi4Ti3O 12 The molar ratio of the nanosheets was 0.4:1), and after reacting at room temperature for 30 min, the surface-modified Bi4Ti3O 12 , repeatedly treated with deionized water and ethanol to remove soluble impurities; then, dried in a vacuum oven at 60 °C for 12 h to obtain Bi / Bi4Ti3O 12 -OVs (i.e., bismuth titanate nanosheets co-modified with bismuth element and oxygen defects).
[0063] The Bi / Bi4Ti3O synthesized in this example 12 -OVs catalyst phase analysis XRD Figure 3 As shown in the figure, it can be seen that the diffraction peak corresponding to Bi single substance exists, proving the successful in-situ growth of Bi single substance; Bi / Bi4Ti3O 12 -TEM and HRTEM of OVs catalysts Figure 4 As shown, from Figure 4 It can be seen that Bi / Bi4Ti3O 12 -OVs catalysts are all in the form of nanosheets. In addition, Bi / Bi4Ti3O 12 -OVs nanosheets have clear particles on the edge, which are single bismuth particles, that is, Bi / Bi4Ti3O 12 -OVs substances;
[0064] For the Bi4Ti3O 12and Bi / Bi4Ti3O 12 -OVs photocatalyst was subjected to EPR analysis, and the results were as follows Figure 5 As shown, the existence of oxygen defects is proved, and it is found that the obtained Bi / Bi4Ti3O 12 -OVs have a higher 12 More abundant oxygen defects.
[0065] For the Bi4Ti3O 12 and Bi / Bi4Ti3O 12 -OVs photocatalysts for fluorescence lifetime (e.g. Figure 6 ) and photocurrent analysis (as shown Figure 7 shown), Bi / Bi4Ti3O 12 -OVs catalyst is better than Bi4Ti3O 12 After being excited by light, the catalyst can generate more photogenerated carriers and have a longer carrier lifetime.
[0066] Example 3: Study on the effect of catalyst on NO purification x Application in pollutants
[0067] 1) Bi4Ti3O 12 Catalytic performance test of nanosheets:
[0068] Weigh 0.2 g of Bi4Ti3O prepared in Example 1 12 The nanosheet powder was poured into a Petri dish with a diameter of 12 cm, an appropriate amount of ethanol was added, ultrasonic treatment was performed for 5 min, uniform dispersion was achieved, and then the powder was placed in an oven at 60 °C and dried for 30 min.
[0069] After drying, Bi4Ti3O 12 The photocatalytic performance of the nanosheet powder was tested using a continuous flow reactor. The specific test conditions were as follows: relative humidity was 60%; oxygen content was 21%; the flow rate of NO gas was 3.3 L / min; NO and air were completely mixed to make the initial NO concentration around 550 ppb, the amount of catalyst was 0.2 g, and the light source was a 150 W halogen tungsten lamp. The performance of removing NO under illumination was tested. After 30 minutes of illumination, the NO removal rate was 40.5%, and the highest NO2 concentration reached 400 ppb. The results are shown in Table 1.
[0070] 2) Bi / Bi4Ti3O 12 -Catalytic performance test of OVs
[0071] Weigh 0.2 g of Bi / Bi4Ti3O prepared in Example 2 12 -OVs were poured into a culture dish with a diameter of 12 cm, and an appropriate amount of ethanol was added. The dish was ultrasonically treated for 5 min, dispersed evenly, and then placed in an oven at 60 °C and dried for 30 min.
[0072] The dried Bi / Bi4Ti3O 12 -OVs uses a continuous flow reactor to test the photocatalytic performance. The specific test conditions are as follows: relative humidity is 60%; oxygen content is 21%; the flow rate of NO gas flow is 3.3L / min; NO and air are completely mixed to make the initial NO concentration about 550ppb, the amount of catalyst is 0.2g, and the light source is a 150W halogen tungsten lamp. The performance of removing NO under light conditions is tested. Under 30 minutes of light, the NO removal rate reaches 61.2%, and the highest NO2 concentration is 117ppb, which has excellent efficiency in deep removal of nitrogen oxides. The results are shown in Table 1.
[0073] Table 1Bi4Ti3O 12 and Bi / Bi4Ti3O 12 Photocatalytic degradation performance of NO with -OVs catalyst
[0074]
[0075] From the data in Table 1, it can be seen that Bi4Ti3O modified by elemental bismuth and oxygen defects 12 Compared with unmodified Bi4Ti3O 12 It has better photocatalytic performance for deep oxidation of NO.
[0076] The Bi4Ti3O 12 Nanosheets and Bi / Bi4Ti3O 12 The NO concentration change within 30 minutes of the photocatalytic degradation of NO by -OVs catalyst is shown in the figure Figure 8 The corresponding NO2 concentration change diagram is shown in Fig. 9 As shown, Bi / Bi4Ti3O 12 -OVs catalyst photocatalytic degradation of NO reaction cycle test diagram Fig.10 As shown. Figure 8-Figure 10 It can be seen that Bi / Bi4Ti3O 12 -OVs catalyst can stably and efficiently deeply oxidize NO to nitrate.
[0077] Example 4: Exploring different NaBH4 / Bi4Ti3O 12 Effect of molar ratio on catalytic performance
[0078] Weigh 1.0 g of original Bi4Ti3O 12 The nanosheet powder (prepared in Example 1) was added to 50 mL of deionized water and stirred for 30 min. 12 In the suspension, 20 mL of NaBH4 solution (NaBH4 / Bi4Ti3O 12The molar ratios were 0.2:1, 0.4:1 and 0.6:1 respectively); after 30 min of reaction, the surface-modified Bi4Ti3O 12 , and repeatedly treated with deionized water and ethanol to remove soluble impurities. Then, dried in a vacuum oven at 60 °C for 12 hours to obtain Bi / Bi4Ti3O 12 -OVs(1:5),Bi / Bi4Ti3O 12 -OVs(2:5) and Bi / Bi4Ti3O 12 -OVs(3:5).
[0079] Referring to the photocatalytic performance test method of Example 3, the Bi / Bi4Ti3O 12 The NO concentration change within 30 minutes of the photocatalytic degradation of NO by -OVs catalyst is shown in the figure Fig.11 The corresponding NO2 concentration change diagram is shown in Fig.12 As shown in the figure, it can be obtained that NaBH4 / Bi4Ti3O 12 When the molar ratio is 0.4:1, the NO removal efficiency is the highest, which is the optimal catalyst for this technical solution.
[0080] The Bi / Bi4Ti3O 12 -OVs(1:5),Bi / Bi4Ti3O 12 -OVs(2:5) and Bi / Bi4Ti3O 12 The NO concentration change within 30 minutes of the photocatalytic degradation of NO by -OVs (3:5) catalyst is shown in the figure Fig.11 The corresponding NO2 concentration change diagram is shown in Fig.12 As shown, from Fig.11 and Fig.12 It can be seen that Bi / Bi4Ti3O 12 -OVs(2:5) catalyst relative to Bi4Ti3O 12 The catalyst and other proportion catalysts have better photocatalytic deep oxidation performance of NO.
[0081] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing bismuth titanate nanosheets co-modified with bismuth and oxygen defects, characterized in that: The steps include: 1) Dispersing bismuth and titanium precursors in an alkaline solution in sequence to obtain a bismuth-titanium suspension; 2) adding a surfactant to the bismuth-titanium suspension, and reacting the suspension at a constant temperature in an oven to obtain bismuth titanate nanosheets; 3) The reducing agent and the bismuth titanate nanosheets are dispersed in deionized water respectively, and mixed with magnetic stirring at room temperature to obtain bismuth titanate nanosheets co-modified with bismuth element and oxygen defects by wet chemical deposition.
2. The method for preparing bismuth titanate nanosheets co-modified with bismuth element and oxygen defects according to claim 1, characterized in that: The precursor of bismuth is bismuth nitrate.
3. The method for preparing bismuth titanate nanosheets co-modified with bismuth element and oxygen defects according to claim 1, characterized in that: The titanium precursor is tetrabutyl titanate.
4. The method for preparing bismuth titanate nanosheets co-modified with bismuth element and oxygen defects according to claim 1, characterized in that: The surfactant is sodium oleate.
5. The method for preparing bismuth titanate nanosheets co-modified with bismuth element and oxygen defects according to claim 4, characterized in that: The process conditions of the oven constant temperature reaction in step 2) are: reaction temperature is 180° C., and reaction time is 20 h.
6. The method for preparing bismuth titanate nanosheets co-modified with bismuth element and oxygen defects according to claim 1, characterized in that: The mass ratio of the bismuth precursor to the volume ratio of the titanium precursor in step 1) is (1-2) g: (0.5-1.5) mL.
7. The method for preparing bismuth titanate nanosheets co-modified with bismuth element and oxygen defects according to claim 1, characterized in that: In step 3), the molar ratio of the reducing agent to the bismuth titanate nanosheets is (0.2-0.6):1; and the reducing agent is sodium borohydride.
8. A bismuth titanate nanosheet co-modified with bismuth element and oxygen defects prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the bismuth titanate nanosheets co-modified with bismuth element and oxygen defects as claimed in claim 8 in photocatalytic removal of nitrogen oxides.